Hand hygiene adherence and associated factors among nursing staff in long-term care facilities: A cross-sectional study - Eunkyo Kim; Eunhee Cho; Gwang Suk Kim; Kyung Hee Lee (Journal of Korean Gerontological Nursing, 2026)
Purpose: Despite the critical importance of hand hygiene (HH) in long-term care facilities, research on adherence and its determinants in these settings remains scarce. This study examined HH adherence and its associated factors among nursing staff in long-term care facilities. Methods: This cross-sectional study surveyed 128 nursing staff members (registered nurses, n=78; nurse assistants, n=50). Data were collected from 35 long-term care facilities across South Korea. HH adherence was calculated from self-reported HH performances and opportunities based on the WHO Five Moments, and HH perception and infrastructure were assessed using adapted WHO-based instruments. Results: The mean clinical experience of participants was 14.58±10.12 years. The HH adherence rate was 70.85%. The mean scores of HH perception and infrastructure were 73.41±11.65 out of 84 points and 32.42±5.18 out of 40 points, respectively. HH adherence was significantly associated with infrastructure (β=0.22, p=.042) and working in a specialized unit (β=0.22, p=.013). Conclusion: This study identified HH infrastructure quality and working in specialized units as significant factors associated with HH adherence among nursing staff in long-term care facilities. These findings suggest that strengthening HH infrastructure and considering unit-level working conditions may contribute to improved adherence. Facility-wide multimodal strategies that combine infrastructure improvement with ongoing education are recommended to sustain HH practices in long-term care settings. Future research should examine system-level and organizational factors using multilevel designs to further elucidate determinants of HH adherence in these settings.